Selpercatinib combination with the mitochondria-targeted antioxidant MitoQ effectively suppresses RET–mutant thyroid cancer - Wenjing Chen; Sophie Dream; Pui-Yin Leung; Pui-Kei Wu; Stuart Wong; Jong-In Park (npj Precision Oncology, 2024)
Abstract Genetic alternation of REarranged during Transfection (RET) that leads to constitutive RET activation is a crucial etiological factor for thyroid cancer. RET is known to regulate mitochondrial processes, although the underlying molecular mechanisms remain unclear. We previously showed that the multi-kinase inhibitors vandetanib and cabozantinib increase the mitochondrial membrane potential (Δψm) in RET-mutated thyroid tumor cells and that this effect can be exploited to increase mitochondrial enrichment of Δψm-sensitive agents in the tumor cells. In this study, we hypothesized that the RET-selective inhibitor, selpercatinib, can increase Δψm and, subsequently, tumor cell uptake of the mitochondria-targeted ubiquinone (MitoQ) to the level to break the mitochondrial homeostasis and induce lethal responses in RET-mutated thyroid tumor cells. We show that selpercatinib significantly increased Δψm, and its combination with MitoQ synergistically suppressed RET-mutated human thyroid tumor cells, which we validated using RET-targeted genetic approaches. Selpercatinib and MitoQ, in combination, also suppressed CCDC6-RET fusion cell line xenografts in mice and prolonged animal survival more effectively than single treatments of each agent. Moreover, we treated two patients with CCDC6-RET or RET M918T thyroid cancer, who could not take selpercatinib at regular doses due to adverse effects, with a dose-reduced selpercatinib and MitoQ combination. In response to this combination therapy, both patients showed tumor reduction. The quality of life of one patient significantly improved over a year until the tumor relapsed. This combination of selpercatinib with MitoQ may have therapeutic potential for patients with RET-mutated tumors and intolerant to regular selpercatinib doses.